Identification of functional lipid metabolism biomarkers of brown adipose tissue aging - Sabrina Gohlke (Molecular Metabolism, 2019)
Objective: Aging is accompanied by loss of brown adipocytes and a decline in their thermogenic potential, which may exacerbate the development of adiposity and other metabolic disorders. Presently, only limited evidence exists describing the molecular alterations leading to impaired brown adipogenesis with aging and the contribution of these processes to changes of systemic energy metabolism. Methods: Samples of young and aged murine brown and white adipose tissue were used to compare age-related changes of brown adipogenic gene expression and thermogenesis-related lipid mobilization. To identify potential markers of brown adipose tissue aging, non-targeted proteomic and metabolomic as well as targeted lipid analyses were conducted on young and aged tissue samples. Subsequently, the effects of several candidate lipid classes on brown adipocyte function were examined. Results: Corroborating previous reports of reduced expression of uncoupling protein-1, we observe impaired signaling required for lipid mobilization in aged brown fat after adrenergic stimulation. Omics analyses additionally confirm the age-related impairment of lipid homeostasis and reveal the accumulation of specific lipid classes, including certain sphingolipids, ceramides, and dolichols in aged brown fat. While ceramides as well as enzymes of dolichol metabolism inhibit brown adipogenesis, inhibition of sphingosine 1-phosphate receptor 2 induces brown adipocyte differentiation. Conclusions: Our functional analyses show that changes in specific lipid species, as observed during aging, may contribute to reduced thermogenic potential. They thus uncover potential biomarkers of aging as well as molecular mechanisms that could contribute to the degradation of brown adipocytes, thereby providing potential treatment strategies of age-related metabolic conditions. Keywords: Brown adipose tissue, Aging, Ceramides, Sphingolipids, Dolichol lipids